Performance optimization of a hybrid PV/T solar system using Soybean oil/MXene nanofluids as A new class of heat transfer fluids - Rubbi, F. (Elsevier Ltd, 2020)
In this research, a new class of nanofluid is successfully formulated from Soybean oil and MXene (Ti3C2) particles to implement as working fluid on a hybrid photovoltaic-thermal (PV/T) solar collector for performance optimization. This study emphasizes on the preparation of the Soybean oil/MXene (SO/Ti3C2) nanofluid, optical and thermal characterization of the nanofluid including suspension stability. The SO/Ti3C2 nanofluid samples are formulated suspending two-dimensional (2D) MXene particles at 0.025â0.125 wt concentrations into pure Soybean oil. SEM, UVâvis, FTIR and TGA analysis are performed for morphology, optical and thermal stability characterization respectively. Achieved thermal conductivity results of SO/Ti3C2 nanofluid for 0.125 wt of Ti3C2 exhibited 60.82 enhancement at 55 Â°C compared to pure Soybean oil. The specific heat capacity (cp) of formulated nanofluids is measured employing a differential scanning calorimeter (DSC). Maximum cp augmentation is found to be 24.49 at 0.125 wt loading of Ti3C2 in the base oil. Numerical implementation of the prepared SO/Ti3C2 nanofluids on PV/T is performed using COMSOL Multiphysics software resulted noteworthy improvement compared to conventional water, Alumina/water and MXene/palm oil nanofluids as working fluid. Overall thermal effectiveness of the PV/T system is achieved 84.25 using SO/Ti3C2 nanofluids at 0.07 kg/s mass flow rate. Furthermore, employing the nanofluids electrical output of the PV/T is improved by 15.44 in comparison with water/alumina nanofluids at an irradiance of 1000 W/m2 and mass flow rate of 0.07 kg/s. The stated findings indicate overall effectiveness of the Soybean oil based MXene nanofluids over conventional fluids used for cooling purpose in the PV/T collector. Â© 2020 International Solar Energy Society